Impact of zoning heating and air conditioning control systems in users comfort and energy efficiency in residential buildings - Fernández-Hernández, Francisco Ángel; Peña Suárez, José Miguel; Bandera Cantalejo, Juan Antonio; González Muriano, María del Carmen (Elsevier, 2022)
Nowadays, in the residential sector, a widely used heating, ventilation and air conditioning system is the ducted direct expansion inverter system based on the on/off control of a single zone, which cannot guarantee the thermal comfort in each room of the building. As a solution, the standard EN 15,232 regulates the use of control systems including thermal zoning as a fundamental condition in the energy efficiency in buildings. The zoning system can adapt the equipment working regime to meet the thermal demand in each zone monitoring the air temperature according to users’ preferences ensuring the thermal comfort in each zone. Framed in this goal, in contrast to complex and costly control systems, this paper presents a new zoned control system based on thermostats and motorized dampers in each zone, a control board and a communication gateway which allows the communication between the unit and the control board to set operational parameters as the speed of the fan or the supply air set point temperature. The practical feasibility of this new control system is presented with a thermo-economic comparison analysis with respect the conventional in the context of the Building Research Establishment Environmental Assessment Methodology certification scheme. The model of the zoning system together with implemented control algorithms is developed in TRNSYS17 and the case of study is a residential dwelling in three different Spanish cities. The results show how the thermal zoning control contributes to adapt the thermal energy to each zone in a more efficient way. Moreover, the regulation of the motorized dampers, fan speed and set point temperature of the unit ensures the thermal comfort in all the zones of the building guaranteeing a category B according to the standard regulations. Finally, from the point of view of energy consumption, energy savings from 21 to 42% are obtained, resulting in payback periods of the installation from 3.2 to 4.3 years
Keywords: Sistemas de control inteligente; Ingeniería sostenible; Aire acondicionado; Ventilación; HVAC control system; Energy efficiency in buildings; Sustainability certification methods; Thermal simulation; Smart system